Oxidation of 1-Alkylthioureas: Formation of 3-Alkylimino- 4-Alkyl-5-Imino-Δ2-1,2,4-Thiadiazolines - V. Nair, Sheena (Asian Journal of Chemistry, 2010)
Oxidation of certain 1-alkylthioureas has been found to follow the overall pattern as observed in the case of 1-aryl and 1-aryl-3- alkyl substituted thioureas. The primary product in all cases is the corresponding bis(substituted formarnidine) disulphide salt which eliminates an atom of sulphur affording the related monosulphide salt which rearranges into the isomeric arnidinothiourea These on further oxidation form the corresponding 1,2,4-thiadiazolines. Their structures have been established by chemical degradation and spectral, studies.